Leishmania major adenylate kinase immunization offers partial protection to a susceptible host. (27th January 2020) - Zutshi, Shubhranshu; Kumar, Sunil; Sarode, Aditya; Roy, Somenath; Sarkar, Arup; Saha, Bhaskar
Abstract: Leishmania major causes mild‐to‐severe cutaneous lesions resulting in significant disfigurations, if untreated. The drugs are toxic, and drug‐resistance parasites are emerging. Therefore, a prophylactic vaccination is an urgent need. As no vaccine is available, we compared the genes expressed by virulent and avirulent parasites. We identify L major adenylate kinase (AdeK) as a probable vaccine candidate after a series of experimentations. We cloned the gene in mammalian pcDNA6/HisA and pet28a + vector for in vivo expression following immunization and in vitro protein expression for booster, respectively. We observed that immunization of susceptible BALB/c mice with AdeK resulted in significant protection against L major challenge infection. The protection was accompanied by increased IFN‐γ producing lymphocytes and reduced IL‐4, IL‐17 and IL‐10 secreting central and effector Th2, Th17 and Treg memory cells, respectively. These observations indicate L major AdeK as a potential vaccine candidate.